Alzheimer''s Association® TrialMatch™: a next-generation resource for matching patients to clinical trials in Alzheimer''s disease and related disorders. (February 2012) - Petersen, Ronald C; Nixon, Ralph A; Thies, William; Taylor, Arnetti; Geiger, Angela Timashenka; Cordell, Cyndy
SUMMARY Many clinical trials for Alzheimer''s disease and related disorders struggle to achieve enrollment goals, hampering the progress of research. To help address this problem, the Alzheimer''s Association® has developed and implemented a new clinical trial-matching service designed to increase awareness of ongoing clinical trials among potential participants, improve initial matching of potential participants to enrollment criteria and thus help investigators achieve enrollment goals. This service, Alzheimer''s Association TrialMatch™, uses numerous personal and disease characteristics to match users with potential clinical trials that are currently enrolling participants. It provides users with direct access to trained professional consultants who interpret and explain an individual''s eligibility for specific clinical trials and is designed for use by patients, caregivers, healthy volunteers, physicians and other healthcare providers and researchers. During the first year of operation (July 2010–June 2011), the service received almost 45, 000 queries and more than 11, 000 completed profiles, which led to 2784 referrals to clinical trials. At least 163 participants of the service are known to have enrolled in a clinical trial. Participants self-report their enrollment into trials.